Conditioned Media of Human Umbilical Cord Blood Mesenchymal Stem Cell Inhibits Ultraviolet B-induced Apoptosis in Fibroblasts - Dian Andriani Ratna Dewi; Ferry Sandra (The Prodia Education and Research Institute (PERI), 2019)
BACKGROUND: Ultraviolet (UV)B irradiated-skin cells may respond either by activating protective or apoptotic mechanisms. Several treatments has been reported to prevent apoptosis of the skin cell. To date, despite of the cell, secretome of mesenchymal stem cell (MSC) has been progressively explored for various treatment. Current research was conducted to find out the possible effect of MSC's secretome to protect normal cells from the UVB irradiation.METHODS: For preparation of the conditioned media human umbilical cord blood mesenchymal stem cell (CM-hUCB-MSC), hUCB was collected and separated to collect mononuclear cell (MNC). MNC was cultured in MSC medium until passage 4, then checked for MSC biomarkers. Conditioned media was then produced from the cultured MSC. For induction of apoptosis, NIH3T3 cells were pretreated with/without CM-hUCB-MSC, prior to the UVB irradiation for 5-60 minutes. After 24 hours, apoptosis evaluation was conducted with Sub-G1 assay with hypotonic fluorochrome solution using flow cytometer.RESULTS: The average of apoptotic cells irradiated with UVB for 30 minutes was 94.2%. The 30-minutes-UVB irradiation significantly induced apoptosis in NIH3T3 cells (p=0.000). The averages of apoptotic cells by pretreatment of 0, 5, 10 and 20% CM-hUCB-MSC prior to UVB irradiation were 94.2, 46.8, 31.8 and 31.5 %, respectively. The pretreatment of 5, 10 and 20% CM-hUCB-MSC prior to UVB irradiation could significantly decrease the percentage of apoptosis caused by UVB (p=0.001).CONCLUSION: Taken together, CM-hUCB-MSC inhibited UVB-induced apoptosis in NIH3T3 cells significantly, suggesting that CM-hUCB-MSC might be a potential anti-UVB-induced apoptosis factor. Hence, further research should be explored to disclose its specific intracellular mechanism.KEYWORDS: UVB, stem cell, conditioned media, fibroblast, apoptosis, aging, secretome, NIH3T3 cell